2018
DOI: 10.1075/itl.00011.jel
|View full text |Cite
|
Sign up to set email alerts
|

Examining incidental vocabulary acquisition from captioned video

Abstract: Previous comparisons of vocabulary uptake from captioned and uncaptioned audio-visual materials have almost consistently furnished evidence in favour of captioned materials. However, it is possible that many such comparative studies gave an advantage to the captioned input conditions by virtue of their use of written word prompts in the tests. The present study therefore examines whether aurally presented test prompts yield equally compelling evidence for the superiority of captioned over uncaptioned video. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The positive effects of captions compared to no on-screen text support the work of other studies (e.g., Mohd Jelani & Boers, 2018;Montero Perez et al, 2014;Sydorenko, 2010;Winke et al, 2010). Eye-tracking research has shown that foreign language learners' use of captions is high (Winke et al, 2013) and that captions are perceived as helpful for form-meaning mapping (Montero Perez et al, 2013a;Winke et al, 2013).…”
Section: On-screen Text In Audiovisual Inputsupporting
confidence: 84%
See 3 more Smart Citations
“…The positive effects of captions compared to no on-screen text support the work of other studies (e.g., Mohd Jelani & Boers, 2018;Montero Perez et al, 2014;Sydorenko, 2010;Winke et al, 2010). Eye-tracking research has shown that foreign language learners' use of captions is high (Winke et al, 2013) and that captions are perceived as helpful for form-meaning mapping (Montero Perez et al, 2013a;Winke et al, 2013).…”
Section: On-screen Text In Audiovisual Inputsupporting
confidence: 84%
“…Although both the written and spoken form were provided in the tests, learners in the captions group might have relied mostly on the written form. Previous research (Mohd Jelani & Boers, ; Sydorenko, ) has shown that the benefits of captions might be due to written prompts. Future research should investigate to what extent captions promote the learning of the written or the spoken word form.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A further explanation for the present findings is the use of video in the glosses. In this context, Aldera and Mohsen (2013), Jelani and Boers (2018) as well as Cokely and Muñoz (2019) found out that using videos is an effective means that can enhance vocabulary acquisition. This explanation is supported by the assumptions of the GTML (Mayer, 2005) which assumes that the working memory has a limited capacity, therefore there should be a simultaneous processing of verbal and visual information (Türk & Erçetin, 2012).…”
Section: Discussionmentioning
confidence: 98%